Anomalous heat transfer enhancement by slip due to nanofluids in circular concentric pipes. (June 2015) - Turkyilmazoglu, Mustafa
Abstract: Convective heat transfer of nanofluids in circular concentric pipes under the influence of partial velocity slips on the surfaces and the resulting anomalous heat transfer enhancement are investigated in the present paper. Single phase nanofluid model is employed to get fully developed exact laminar flow and temperature fields accounting for the thermal boundary conditions of both the heated outer wall with the inner wall insulated and the heated inner wall with the outer wall insulated. The presented closed-form solutions of velocity and temperature fields as well as the Nusselt number derivation are able to explain the slip effects on different nanofluids and their contribution to anomaly level of enhancement in the rate of heat transfer, which is the main interest of the recent literature. Results clearly indicate that the anomalous heat transfer enhancement as observed in the experiments and numerical solutions of nanofluid flows occurring in the circular concentric shapes is mainly due to the velocity slip mechanism.